Physical properties of abaca (Musa textilis nee) fibre reinforced high impact polystyrene (HIPS) composites - Hadi, Agung Efriyo; Salit, Mohd Sapuan; Megat Ahmad, Megat Mohamad Hamdan; Mohd Dahlan, Khairul Zaman; Usman, Mustofa (Universiti Putra Malaysia Press, 2011)
The physical properties by natural fibre have a great importance, specifically in the structural of natural fibre which reinforces matrix. Response surface methodology with Box-Behnken (BB) design of experiment was utilized to study water absorption and melt flow index (MFI) of abaca fibre reinforced high impact polystyrene (HIPS) composites. The design utilizes fraction of weight abaca fibre, maleic anhydride (MAH), and impact modifier to develop models for characteristic behaviours of water absorption and MFI of composites. Abaca fibre reinforced high impact polystyrene (HIPS) composites were produced with different fibre loadings (30, 40, and 50 wt%), different compositions of coupling agent, maleic anhydried (MAH) (1, 2, and 3 wt%) and different compositions of impact modifier (4, 5, 6 wt%). The individual optimum of water absorption was found when loading abaca fibre close to 34.61 wt%, maleic anhydride 1 wt%, and impact modifier 4.01 wt%. The individual optimum of melt flow index dealt with loading abaca fibre 36.71 wt%, maleic anhydride 3 wt% and impact modifier 4.02 wt%. Meanwhile, the optimum condition for water absorption of abaca fibre reinforced HIPS composites was followed by a decreasing trend of the value of melt flow index.